A new approach to understand the deformation behavior and strengthening mechanism of molybdenum alloy: From single crystal to polycrystal. (January 2022) - Jiao, Benqi; Zhao, Qinyang; Zhao, Yongqing; Zhang, Wen; Li, Yanchao; Hu, Zhongwu; Gao, Xuanqiao; Cui, Changxing; Wu, Mingming; Xin, Tian
Abstract: The deformation behavior and strengthening mechanism for Mo-3Nb single crystal with 〈111〉 orientation and polycrystal have been investigated and disclosed comprehensively in a wide temperature range by quasi-static compression with 7% plastic strain. The slip traces of single crystal and polycrystal at room temperature show different features, which long continuous slip traces appear on the surface of deformed Mo-3Nb single crystals while some branch-off slip lines can only be observed in large grains for polycrystals. The conjugate slip planes of single crystals are activated at the elevated temperature, while the slip lines of polycrystals are difficult to be observed because of the grain boundary sliding effect. The compressive stress of single crystals and polycrystals shows different results at different deformation temperatures, suggesting that grain boundaries in polycrystals play an important role in the strengthening mechanism. TEM analysis shows that dislocation entanglement is the main strengthening mechanism both in single crystal and polycrystal during the room temperature deformation. With the increase of temperature, the strengthening mechanism caused by dislocation entanglement becomes ineffective, while grain boundaries continue to hinder the dislocation movement and the strengthening effect greatly weakened due to the dynamic recovery. Graphical abstract: Unlabelled Image Highlights: <111> oriented Mo-3Nb single crystal and polycrystal have been firstly designed Different slip features are observed between single crystal and polycrystal The grain boundary strengthening effect weakens when the deformation temperature reaches to 1500 °C